Evaluating interventions that prevent or counter violent extremism: A practical guide - Hofman, Joanna; Sutherland, Alex (RAND Corporation, 2018)

Insights for Influence: Understanding Impact Pathways in Crisis Response - Clark, Louise; Carpenter, Jo; Taylor, Joe (Institute of Development Studies, 2023)
The Covid-19 Responses for Equity (CORE) programme was a three-year initiative funded by the Canadian International Development Research Centre (IDRC) that brought together 20 projects from across the global South to understand the socioeconomic impacts of the Covid-19 pandemic, improve existing responses, and generate better policy options for recovery. The research covered 42 countries across Africa, Asia, Latin America, and the Middle East to understand the ways in which the pandemic affected the most vulnerable people and regions, and deepened existing vulnerabilities. Research projects covered a broad range of themes, including macroeconomic policies for support and recovery; supporting essential economic activity and protecting informal businesses, small producers, and women workers; and promoting democratic governance to strengthen accountability, social inclusion, and civil engagement. The Institute of Development Studies (IDS) provided knowledge translation (KT) support to CORE research partners to maximise the learning generated across the research portfolio and deepen engagement with governments, civil society, and the scientific community. As part of this support, the IDS KT team worked with CORE project teams to reconstruct and reflect on their impact pathways to facilitate South-South knowledge exchange on effective strategies for research impact, and share learning on how the CORE cohort has influenced policy and delivered change. This report presents an overview of these impact pathways and the lessons learnt from a selection of the projects chosen to represent the diversity of approaches to engage policymakers, civil society, and the media to generate and share evidence of the effect of the pandemic on diverse vulnerable groups.
Accepted: 2023-11-10T12:56:06Z Publisher: Institute of Development Studies

Multiple case study analysis - Stake, Robert E. (The Guilford Press, 2006)
Examining situational complexity is a vital part of social and behavioral science research. This engaging text provides an effective process for studying multiple cases–such as sets of teachers, staff development sessions, or clinics operating in different locations–within one complex program. The process also can be used to investigate broadly occurring phenomena without programmatic links, such as leadership or sibling rivalry. Readers learn to design, analyze, and report studies that balance common issues across the group of cases with the unique features and context of each case. Three actual case reports from a transnational early childhood program illustrate the author's approach, and helpful reproducible worksheets facilitate multicase recording and analysis.
Keywords: Case method; Cross-cultural studies; Education; Europe; Eastern; Research Methodology; Step by Step (Program)